Piroplazmoza konja - Gotić, Jelena; Crnogaj, Martina; Šmit, Iva; Brkljača Bottegaro, Nika; Grden, Darko, veterinar; Mrljak, Vladimir; Beck, Relja (2020)
Piroplazmoza je hemoprotozojska bolest široke geografske rasprostranjenosti i svjetskog značenja. U kopitara piroplazmozu prouzroče paraziti Theileria equi i Babesia caballi. Pojava piroplazmoze usko je vezana uz geografsku rasprostranjenost i sezonsku aktivnost vektora, krpelja šikare (fam. Ixodidae). Intrareritrocitne piroplazme T. equi i B. caballi prouzroče akutnu, supakutnu ili kroničnu bolest u kopitara, a mogu prouzročiti i neonatalnu piroplazmozu, a u kobila i pobačaj. Patogenost i klinička manifestacija nisu jednaki za oba uzročnika piroplazmoze konja, a njihove su razlike rezultat specifičnosti životnih ciklusa tih protozoa. Veliki broj konja ostaje supklinički invadirano s niskom parazitemijom i inaparentnom bolesti. Dijagnostika piroplazmoze konja se provodi izravnim (dokaz uzročnika) i neizravnim metodama (dokaz specifičnih protutijela). Diferencijalne dijagnoze piroplazmoze konja uključuju influencu, infekcioznu anemiju kopitara te anaplazmozu i boreliozu kao znatne krpeljima prenosive bolesti konja.
Equine piroplasmosis is a haemoprotozoic disease of wide geographical distribution and worldwide significance, caused by two haemoprotozoans, Theileria equi and Babesia caballi. The occurrence of piroplasmosis is closely related to the geographical distribution and seasonal activity of the carriers of ixodid ticks. Intraerytocytic piroplasms of T. equi and B. caballi cause acute, subacute or chronic disease in equines, and may also cause neonatal babesiosis and abortion in mares. Pathogenicity and clinical manifestation differ for each of the causative agents of piroplasmosis, due to their specific life cycles. Many horses remain subclinically infected with low parasitemia and inapparent disease. Diagnosis of horse piroplasmosis is performed by direct (evidence of the parasite) and indirect methods (evidence of specific antibodies). Differential diagnoses of equine piroplasmosis include equine influenza, equine infectious anaemia, as well as anaplasmosis and borreliosis as significant tick-borne equine diseases.
Bibliografija: 43 jed.
Sažetak ; Summary.
Keywords: Konji -- Piroplazmoza -- Paraziti -- Babesia caballi -- Theileria equi